Recent Advances in Dye Sensitized Solar Cells - Umer Mehmood; Saleem-ur Rahman; Khalil Harrabi; Ibnelwaleed A. Hussein; B. V. S. Reddy (Advances in Materials Science and Engineering)
Solar energy is an abundant and accessible source of renewable energy available on earth, and many types of photovoltaic (PV) devices like organic, inorganic, and hybrid cells have been developed to harness the energy. PV cells directly convert solar radiation into electricity without affecting the environment. Although silicon based solar cells (inorganic cells) are widely used because of their high efficiency, they are rigid and manufacturing costs are high. Researchers have focused on organic solar cells to overcome these disadvantages. DSSCs comprise a sensitized semiconductor (photoelectrode) and a catalytic electrode (counter electrode) with an electrolyte sandwiched between them and their efficiency depends on many factors. The maximum electrical conversion efficiency of DSSCs attained so far is 11.1%, which is still low for commercial applications. This review examines the working principle, factors affecting the efficiency, and key challenges facing DSSCs.